A Thin‐Film Flexible Defect‐Mode Laser. Issue 8 (24th February 2020) - Ali, Taimoor; Lin, Jia‐De; Snow, Benjamin; Wang, Xiuze; Elston, Steve J.; Morris, Stephen M.
Abstract: Laser emission from a flexible defect‐mode structure consisting of two photopolymerized liquid crystal thin films separated by a dye‐doped polymethylmethacrylate defect layer is demonstrated. A simple and cost‐effective film transfer technique is used to fabricate the flexible laser and the corresponding laser emission characteristics, which shows single‐mode laser emission at λ = 582 nm, with an excitation threshold of E th = 12.3 ± 0.5 µJ cm −2 per pulse and a slope efficiency of ηs = 6.0 ± 0.3%, are presented. The polarization state of the laser emission are also presented and are compared with the findings reported in the literature. Finally, laser‐beam steering is demonstrated up to 42° by subjecting the device to a mechanically induced deformation that creates a radius of curvature of 5 mm, which is of potential interest for conformable and wearable technology platforms. Abstract : A flexible defect‐mode liquid crystal laser fabricated using a facile and cost‐effective film transfer technique is demonstrated. It exhibits a low threshold fluence of 12.3 ± 0.5 µJ cm −2 per pulse. Beam steering is observed when the device is subjected to a mechanical deformation, which shows potential for wearable and flexible technologies.